2019
DOI: 10.1002/cbic.201900390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DNA‐Encoded Disulfide‐ and Thioether‐Cyclized Peptides

Abstract: DNA‐encoded chemical library technologies enable the screening of large combinatorial libraries of chemically and structurally diverse molecules, including short cyclic peptides. A challenge in the combinatorial synthesis of cyclic peptides is the final step, the cyclization of linear peptides that typically suffers from incomplete reactions and large variability between substrates. Several efficient peptide cyclization strategies rely on the modification of thiol groups, such as the formation of disulfide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…An affinity selection of this library against p300 identified two potential inhibitors with single-digit micromolar activity. In addition, the on-DNA Ru-promoted ring-closing metathesis , and thioether cyclization reaction are also viable to be employed to prepare DNA-encode macrocyclic libraries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An affinity selection of this library against p300 identified two potential inhibitors with single-digit micromolar activity. In addition, the on-DNA Ru-promoted ring-closing metathesis , and thioether cyclization reaction are also viable to be employed to prepare DNA-encode macrocyclic libraries.…”
mentioning
confidence: 99%
“…13−16 In 2021, Lu, Chen, and co-workers 17 potential inhibitors with single-digit micromolar activity. In addition, the on-DNA Ru-promoted ring-closing metathesis 18,19 and thioether cyclization reaction 20 are also viable to be employed to prepare DNA-encode macrocyclic libraries. The overall goal in DEL campaigns is to obtain as much selection information as possible to understand the structurebinding relationship (SBR) for hits identification and further optimization.…”
mentioning
confidence: 99%
“…It has been found that disulfide bonds and hydrogen bonds contribute to the stability of native-folded AMPs, and both types of bonds affect the activity of AMPs by influencing their folding stability (Ranade et al 2020;Vila-Perelló et al 2005). In addition to the chemical bonds mentioned in previous sections, a few others have been reported, such as thioether bonds, which are required for peptide maturation (Pham et al 2020;Wieckowski et al 2015). However, the structure-activity relationship between these chemical bonds and AMPs is not clear.…”
Section: Other Factorsmentioning
confidence: 96%
“…Another study on thioether formation was published by Heinis and coworkers describing the formation of macrocycles on DNA in solution by thioether formation. 89 Two tert-butylthio (S-tBu) protected cysteines were incorporated into peptides and subsequently deprotected in aqueous solution. Disulfide bond formation readily occurred, and the addition of symmetrical bis-electrophiles lead to the creation of thioether bonds via nucleophilic substitution or 1,4-addition.…”
Section: Reviewmentioning
confidence: 99%